Osteopetrosis. - Khan, MN; Batta, PK; Hasan, MI; Hossain, MA; Patwary, KH; Ferdous, J (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):715-8. The abstract of this article is available on the PubMed website